Hot fluids, burial metamorphism and thermal histories in the underthrust sediments at IODP 370 site C0023, Nankai Accretionary Complex. (February 2020) - Tsang, Man-Yin; Bowden, Stephen A.; Wang, Zhibin; Mohammed, Abdalla; Tonai, Satoshi; Muirhead, David; Yang, Kiho; Yamamoto, Yuzuru; Kamiya, Nana; Okutsu, Natsumi; Hirose, Takehiro; Kars, Myriam; et al.
Abstract: Drilling during International Ocean Discovery Program (IODP) Expedition 370 at Site C0023 encountered instances of hydrothermal mineralization from 775 to 1121 m below seafloor. Fluid inclusion homogenization temperatures measured on barite veins within this interval indicate precipitation from fluids with temperatures up to 220 °C, and salinities ten times higher than interstitial water (16–25 c.f. 2.8–3.6 wt % NaCl). Patches of stratabound mineralization (rhodochrosite, calcite, barite and anhydride) are largely confined to the vicinity of veins and have vertical thicknesses and extents that can be explained by precipitation within the thermal aureoles of veins. Thermal maturities measured on petroleum biomarkers in underthrust sediments record a rise from pre-oil window to early oil window thermal maturities. Basin models show that increases in thermal maturity can be explained by burial metamorphism, and kinetic-based calculations suggest that hot fluids would only have had a minimal effect on hydrocarbon generation. However, the movement of hot fluids still has geochemical implications and creates a complex thermal history where both short-duration, localized heating within fracture zones at hot temperatures (~200 °C for less than 1 yr) and heating during burial over long durations (80–110 °C for 0.5–2 Myrs) need to be considered. Highlights: Thermal histories for the underthrust domain of the Nankai Accretionary Complex, IODP 370 "Temperature Limits of the Deep Biosphere". Hydrothermal and burial metamorphism at IODP Site C0023 with basin models. Fluid inclusion homogenisation temperatures significantly hotter than present-day formation temperatures. First direct evidence for anomalously hot fluids in underthrust sediments of Nankai Accretionary Complex. Biomarkers in underthrust sediments record rise from pre-oil window to early oil window thermal maturities.